2019
DOI: 10.1021/acs.analchem.9b02207
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bioprinting Application for the Production of Reference Material Containing a Defined Copy Number of Target DNA

Abstract: Nucleic acid amplification methods, such as polymerase chain reaction (PCR), are extensively used in many applications to detect target DNA because of their high sensitivity, good reproducibility, and wide dynamic range of quantification. However, analytical quality control when detecting low copy number target DNA is often missing because of a lack of appropriate reference materials. Recent advances in analytical sciences require a method to accurately quantify DNA at the single molecule level. Herein, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…We considered the specified number of copies to be dispensed as a measured value and calculated the uncertainty of measurements from the production variability and the number of samples used. In addition to the variability of the copy number of intracellular target DNA and the variability because of contamination, which have been evaluated in the previous study 13 , cell aggregation was identified to be another source of the production variability. To increase the production efficiency, two avalanche photodiodes (APD410A/M, Thorlabs; hereinafter referred to as APD) placed oppositely were used to detect any cells in flying droplets (Figure S1 in Supplementary Information File 1).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…We considered the specified number of copies to be dispensed as a measured value and calculated the uncertainty of measurements from the production variability and the number of samples used. In addition to the variability of the copy number of intracellular target DNA and the variability because of contamination, which have been evaluated in the previous study 13 , cell aggregation was identified to be another source of the production variability. To increase the production efficiency, two avalanche photodiodes (APD410A/M, Thorlabs; hereinafter referred to as APD) placed oppositely were used to detect any cells in flying droplets (Figure S1 in Supplementary Information File 1).…”
Section: Resultsmentioning
confidence: 96%
“…The intracellular DNA copy number distribution was measured in the same manner as in the previous study 13 , although a flow cytometer (MA900, Sony) was used for the measurement. In flow cytometry, a cell containing two nuclei cannot be distinguished from an aggregate of two cells containing one nucleus per cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to develop an RNA quantification method that can measure up to one copy of RNA, a standard product in which RNA is dispensed as one copy per well is required. In recent years, although not regarding RNA, standard products have been developed in which DNA is dispensed as one copy/well [104]. In this method, cells are discharged into the well while controlling the number of cells with an inkjet head, instead of dispensing the DNA itself into the well.…”
Section: Methods To Dispense the Solution More Accuratelymentioning
confidence: 99%